The Influence of Fear of Missing Out, Hedonic Shopping Motivation, and Flash Sales on Impulsive Buying during Shopee's Twin Date Promo Event (A Study on Students of Muhammadiyah University Purwokerto) - Najri Aziz; Randikaparsa, Irawan; Rahayu, Tri Septin Muji; Kharismasyah, Alfato Yusnar (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this research is to analyze the influence of Fear of Missing Out, Hedonic Shopping Motivation, and Flash Sales on Impulsive Buying during the Shopee Twin Date Promo Event among Students. This type of research is quantitative, using a purposive sampling technique involving 244 respondents. Data were analyzed using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method to test the relationships between variables. The research results show that fear of missing out, hedonistic shopping motivation, and flash sales positively and significantly impact impulsive buying. The implication of this research is to assist companies in designing effective marketing strategies by leveraging the emotional appeal triggered by FoMO, creating enjoyable shopping experiences to enhance consumers' hedonistic shopping motivation, and utilizing flash sale-based promotions.